Coated sodium ion battery positive electrode material and preparation method thereof
By alumina coating modification of the nickel-manganese base layer oxide, P2-Na0.67Ni1-α-βMnαTiβ material with Al2O3 surface coated with Al and Al doped inside was formed, which solved the problems of low initial capacity and phase transition of the P2-type layered oxide positive electrode material, and achieved higher electrochemical performance and cyclic stability.
Patent Information
- Application Number
- CN202510052993.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
The initial capacity of the P2-type layered sodium oxide battery cathode material is low, which is prone to phase change and affects cycle stability.
By alumina coating modification of the nickel-manganese base layer oxide, a P2-Na0.67Ni1-α-βMnαTiβ material with Al2O3 surface coated with Al and Al doped inside was formed.
It improves the electrochemical performance of the material, enhances circulation stability and air stability, and reduces raw material costs and process complexity.
Smart Images

Figure CN119852366A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of sodium-ion batteries, and particularly relates to a coated sodium-ion battery cathode material and a preparation method thereof. Background Art
[0002] Due to its abundant resources, wide temperature range, and cost-friendly advantages, sodium-ion batteries are considered to be the most potential solution to replace lithium-ion batteries in the energy storage field. Similar to lithium-ion batteries, the electrochemical performance of sodium-ion batteries is largely affected by the cathode material.
[0003] Layered transition metal oxides Na x MO 2 (M = Cr, Mn, Ti, Ni, Co, Fe, etc.), polyanion compounds (Na 3 V 2 (PO 4 ) 3 , Na 2 Fe(SO 4 ) 2 ) and Prussian blue analogues (PBAs) have been widely proven to be candidates for sodium-ion battery cathode materials.
[0004] Among them, layered transition metal oxides are considered to be one of the most promising sodium-ion battery cathode materials due to their excellent electrochemical activity, low cost, and high energy density. The P2-type Na x MnO 2 (0.44 < x ≤ 0.7) material in layered oxides has a wider sodium-ion transport channel and a lower sodium-ion migration energy barrier, and exhibits faster diffusion kinetics. However, the P2-type layered oxide has a lower initial capacity and is prone to P2→O2 phase transformation, which affects the cycle stability. Summary of the Invention
[0005] The purpose of this application is to provide a coated sodium-ion battery cathode material and a preparation method thereof. By performing alumina coating modification on nickel-manganese-based layered oxides, the electrochemical performance of the product material can be effectively improved, and its raw material cost is low, the preparation process is simple, the safety is high, it is environmentally friendly, and it is beneficial to practical production applications.
[0006] The technical solution of this application is as follows:
[0007] On the one hand, an embodiment of this application provides a coated sodium-ion battery cathode material, and its chemical general formula is:
[0008] P2-Na 0.67 Ni 1-α-β Mn α Ti β ;
[0009] Among them, 0<α≤0.67, 0<β≤0.3;
[0010] The above materials are coated with Al 2 O 3 And Al is doped inside.
[0011] Furthermore, in some embodiments of the present application, it is prepared from raw materials including the following components:
[0012] A sodium source, a nickel source, a manganese source, a titanium source, and an aluminum source.
[0013] Furthermore, in some embodiments of the present application, the sodium source is any one or more of sodium carbonate, sodium sulfate, sodium hydroxide, sodium nitrate, and sodium chloride.
[0014] Furthermore, in some embodiments of the present application, the nickel source is any one or more of nickel oxide, nickel hydroxide, nickel nitrate, nickel chloride, nickel sulfate, and nickel acetate.
[0015] Furthermore, in some embodiments of the present application, the manganese source is any one or more of manganese oxide, manganese trioxide, manganese dioxide, manganese nitrate, manganese carbonate, manganese chloride and manganese acetate.
[0016] Furthermore, in some embodiments of the present application, the titanium source is titanium dioxide and / or tetrabutyl titanate.
[0017] Furthermore, in some embodiments of the present application, the aluminum source is any one or more of aluminum nitrate, aluminum oxide, and aluminum isopropoxide.
[0018] On the other hand, the present invention also provides a method for preparing the above-mentioned coated sodium ion battery positive electrode material, and the preparation method comprises the following steps:
[0019] Precursor preparation: Sodium source, nickel source, manganese source, and titanium source are mixed in proportion and ball-milled to obtain a mixed powder, and then the mixed powder is placed in a mold, pressed, sintered at a high temperature, and then cooled and ground to obtain a precursor powder;
[0020] Finished product preparation: Precursor powder is added to a dispersant, and then an aluminum source is added, followed by heating and stirring to obtain a mixed solution, which is then dried, and the dried material is heated and sintered, then cooled, ground and sieved to obtain the product material.
[0021] Further, in some embodiments of the present application, in the above-mentioned precursor preparation step, the temperature is increased to 600-1000° C. at a heating rate of 3-5° C. / min and sintered for 10-24 hours;
[0022] In the above finished product preparation step, the temperature is raised to 300-700° C. at a heating rate of 3-5° C. / min and sintered for 3-8 hours.
[0023] Furthermore, in some embodiments of the present application, in the above-mentioned finished product preparation step, the mass of the added aluminum source is 0.1 to 5 wt % of the mass of the precursor powder.
[0024] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0025] In view of the above aspects, the present invention provides a coated sodium ion battery positive electrode material and a preparation method thereof, wherein the P2 type layered metal oxide Na 0.67 Ni 1-α-β Mn α Ti β The surface of the obtained product material is coated with Al 2 O 3 Shell layer, and its process can dope a small part of the aluminum introduced into the system into the material during the dispersion and sintering preparation process. Among them, aluminum doping can expand the interlayer spacing of layered metal oxide materials, reduce the diffusion barrier of sodium ions, inhibit the structural phase change of materials, inhibit the degradation of the particle surface, and reduce the Jahn-Teller effect of other element ions, thereby improving the kinetics of sodium ion deintercalation; and the alumina coating layer can improve the air stability of the material, inhibit the loss of lattice oxygen and maintain the stability of the electrode material structure. The product material provided by the present application has excellent electrochemical properties, can be applied to the positive electrode of sodium ion batteries, and has high practical value. At the same time, its process flow is simple, the operation is convenient, it can effectively improve production efficiency, improve process safety and stability, and its process raw materials are low in cost, environmentally friendly, and conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 XRD diagrams of materials of Example 1 and Comparative Examples 1-2 of the present application;
[0028] Figure 2 This is the cycle performance diagram of the materials of Example 1 and Comparative Examples 1-2 of the present application at 1C;
[0029] Figure 3This is a cycle performance diagram of the materials of Examples 1 to 3 of the present application at 1C. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] It should be noted that the term "include" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0033] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0034] Example 1
[0035] This embodiment provides a coated sodium ion battery positive electrode material, whose basic material chemical formula is P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 , whose surface is coated with Al 2 O 3 And a small amount of Al is doped inside.
[0036] It is prepared by the following method:
[0037] Precursor preparation: weigh the above raw materials according to the molar ratio of sodium source (anhydrous sodium carbonate): nickel source (nickel oxide): manganese source (manganese trioxide): titanium source (titanium dioxide) = 0.67:0.33:0.37:0.3 and put them into a ball mill (wherein the sodium source is in excess of 2%), add zirconium dioxide balls into the ball mill at a ball-to-material ratio of 1:25 and mix, then seal the ball mill, and ball mill at a speed of 400 rpm for 2 hours to obtain a gray mixed powder;
[0038] The obtained mixed powder was placed in a mold and pressed into a disc with a diameter of 250 mm under a pressure of 20 MPa. The disc was then placed in a crucible and placed in a muffle furnace. The mixture was then heated to 900°C at a heating rate of 3°C / min and sintered for 12 hours. The mixture was then naturally cooled to room temperature and ground in an agate mortar to obtain a precursor powder.
[0039] Finished product preparation: Take 10g of precursor powder, dissolve it in an appropriate amount of dispersant (anhydrous ethanol), and then add 0.1g of aluminum source (aluminum isopropoxide C 9 H 21 AlO 3 ), stirring at a temperature of 70° C. and a stirring rate of 400 r / min for 20 h to obtain a mixed solution;
[0040] The mixed solution was placed in a blast drying oven and dried at 80°C for 12 h. The powdered material obtained by drying was then placed in a crucible and placed in a muffle furnace. The temperature was raised to 600°C at a heating rate of 3°C / min and sintered for 5 h. The mixture was then naturally cooled to room temperature and ground and sieved to obtain the target product P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 @1wt%Al 2 O 3 .
[0041] Example 2
[0042] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:
[0043] In the above-mentioned finished product preparation step, 0.1 g of the aluminum source (aluminum isopropoxide C 9 H 21 AlO 3 ) The dosage is increased to 0.2g;
[0044] The remaining steps and process conditions are the same as those in Example 1;
[0045] The final target product is P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 @2wt%Al 2 O 3 .
[0046] Example 3
[0047] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:
[0048] In the above-mentioned finished product preparation step, 0.1 g of the aluminum source (aluminum isopropoxide C 9 H 21 AlO 3 ) dosage increased to 0.3g;
[0049] The remaining steps and process conditions are the same as those in Example 1;
[0050] The final target product is P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 @3wt%Al 2 O 3 .
[0051] Comparative Example 1
[0052] This comparative example is based on Example 1, and the difference from Example 1 is that:
[0053] In the above finished product preparation step, 10 g of precursor powder and 0.36 g of diammonium hydrogen phosphate were dissolved in an appropriate amount of pure water and stirred for 3 h to obtain a solution material;
[0054] Weigh 0.58 g of aluminum nitrate and dissolve it in anhydrous ethanol, then slowly add it to the solution material, heat and stir at 70° C. and 400 r / min for 24 h to obtain a mixed solution;
[0055] The remaining steps and process parameters are the same as those in Example 1;
[0056] The final target product is P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 @AlPO 4 .
[0057] Comparative Example 2
[0058] This comparative example is based on Example 1, and the difference from Example 1 is that:
[0059] After the precursor powder is obtained through the precursor preparation step, the finished product preparation step is no longer performed;
[0060] The final target product is P2-Na 0.67 Ni 0.33 Mn 0.37 Ti 0.3 O 2 .
[0061] Test example
[0062] The product materials provided in Examples 1 to 3 of the present application and Comparative Examples 1 to 2 were made into button batteries and subjected to electrochemical tests. The specific steps were as follows: the electrode active material, conductive carbon black and binder PVDF were added to a mortar in a mass ratio of 7 (70 wt%): 2 (20 wt%): 1 (10 wt%), and N-methylpyrrolidone was added to grind until mixed; the slurry was then coated on an aluminum foil and transferred to a vacuum drying oven at 80° C. for 12 hours; the electrolyte consisted of 1 M sodium perchlorate dissolved in ethylene carbonate / diethylene carbonate (volume ratio 1:1); and the button batteries were made in a glove box filled with argon; constant current charge and discharge tests were performed on a NEWARE battery testing system, and the cut-off voltage of the sodium ion battery was 2 V to 4.4 V; all tests were performed at room temperature of 26° C.
[0063] The results are shown in Table 1 and Figure 1 to Figure 3 shown.
[0064] Table 1
[0065]
[0066] It can be seen from the results in Table 1 that after the aluminum oxide coating modification (Example 1), compared with the unmodified nickel-manganese-based oxide positive electrode material (Comparative Example 2), the discharge specific capacity and cycle stability of the material can be improved to a certain extent, and the capacity retention rate after 100 cycles is significantly improved. After the surface of the nickel-manganese-based oxide is coated with an aluminum phosphate oxide layer (Comparative Example 1), although the first-cycle discharge specific capacity of the material is improved to a certain extent compared with the unmodified nickel-manganese-based oxide positive electrode material (Comparative Example 2), its cycle stability has not been improved. By comparing the discharge specific capacity of different coating ratios (Examples 1 to 3), it can be seen that when the coating ratio is 1wt% (Example 1), the comprehensive electrochemical performance of the material is the best.
[0067] Figure 1 The XRD diagrams of the materials of Example 1 and Comparative Examples 1-2 are shown in the figure from top to bottom: Comparative Example 1 (blue), Example 1 (red), and Comparative Example 2 (black). It can be seen from the figure that the strong peak at 16.32° is the (002) crystal plane of the P2 phase layered metal oxide positive electrode material, while the peaks at 39.71°, 43.91°, and 49.24° correspond to the (012), (103), and (104) crystal planes of the P2 phase layered metal oxide positive electrode material, respectively, indicating that the coated modified material is still a P2 phase layered metal oxide.
[0068] Figure 2The graphs are the cycle performance of the materials of Example 1 and Comparative Examples 1-2 at 1C. The legends in the graph are Comparative Example 2 (triangle), Example 1 (star), and Comparative Example 1 (pentagon) from top to bottom. It can be seen from the graph that a water-soluble aluminum nitrate is used as an aluminum source in Comparative Example 1. Under the same conditions, the aluminum source forms AlPO on the outside of the material. 4 Coating layer, AlPO 4 The stability of sodium ions will be poor, and the internal crystal structure of the impurities will be affected by factors such as battery polarization and electrolyte degradation. After being assembled into a battery, the battery life will be shorter, and the capacity retention rate after 100 cycles is significantly lower than that of Example 1. This also proves that the aluminum isopropoxide used in Example 1 as an aluminum source greatly improves the electrochemical properties of the coating layer, not only does it not change the phase structure of the nickel-manganese-based oxide, but also has high ionic conductivity, which improves the overall cycle stability.
[0069] Figure 3 The graph is a cycle performance diagram of the materials of Examples 1 to 3 at 1C; the star in the legend is Example 1, the circle is Example 2, and the diamond is Example 3. It can be seen from the figure that using aluminum isopropoxide as an aluminum source through a certain process to convert it into an external aluminum oxide-coated P2 phase nickel-manganese-based layered oxide material doped with Al inside can improve the cycle stability and specific capacity of the P2 phase nickel-manganese-based layered oxide material to a certain extent. Through experimental research, it is known that the optimal coating ratio is 1wt%.
[0070] In summary, the present invention provides a coated sodium ion battery positive electrode material and a preparation method thereof.
[0071] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A coated sodium ion battery positive electrode material, characterized in that: Its general chemical formula is: P2-Na 0.67 Ni 1-α-β Mn α A β ; Among them, 0<α≤0.67, 0<β≤0.3; The material is coated with Al2O3 on the outside and doped with Al on the inside.
2. The coated sodium ion battery positive electrode material according to claim 1, characterized in that: It is prepared from raw materials including the following components: A sodium source, a nickel source, a manganese source, a titanium source, and an aluminum source.
3. The coated sodium ion battery positive electrode material according to claim 2, characterized in that: The sodium source is any one or more of sodium carbonate, sodium sulfate, sodium hydroxide, sodium nitrate, and sodium chloride.
4. The coated sodium ion battery positive electrode material according to claim 2, characterized in that: The nickel source is any one or more of nickel oxide, nickel hydroxide, nickel nitrate, nickel chloride, nickel sulfate, and nickel acetate.
5. The coated sodium ion battery positive electrode material according to claim 2, characterized in that: The manganese source is any one or more of manganese oxide, manganese trioxide, manganese dioxide, manganese nitrate, manganese carbonate, manganese chloride and manganese acetate.
6. The coated sodium ion battery positive electrode material according to claim 2, characterized in that: The titanium source is titanium dioxide and / or tetrabutyl titanate.
7. The coated sodium ion battery positive electrode material according to claim 2, characterized in that: The aluminum source is any one or more of aluminum nitrate, aluminum oxide, and aluminum isopropoxide.
8. A method for preparing a coated sodium ion battery positive electrode material according to any one of claims 1 to 7, characterized in that: The preparation method thereof comprises the following steps: Precursor preparation: Sodium source, nickel source, manganese source, and titanium source are mixed in proportion and ball-milled to obtain a mixed powder, and then the mixed powder is placed in a mold, pressed, sintered at a high temperature, and then cooled and ground to obtain a precursor powder; Finished product preparation: Precursor powder is added to a dispersant, and then an aluminum source is added, followed by heating and stirring to obtain a mixed solution, which is then dried, and the dried material is heated and sintered, then cooled, ground and sieved to obtain the product material.
9. The method for preparing a coated sodium ion battery positive electrode material according to claim 8, characterized in that: In the precursor preparation step, the temperature is raised to 600-1000° C. at a heating rate of 3-5° C. / min and sintered for 10-24 hours; In the step of preparing the finished product, the temperature is raised to 300-700° C. at a heating rate of 3-5° C. / min and sintered for 3-8 hours.
10. The method for preparing a coated sodium ion battery positive electrode material according to claim 8, characterized in that: In the step of preparing the finished product, the mass of the added aluminum source is 0.1 to 5 wt % of the mass of the precursor powder.